Laws of Boolean Algebra:
There are various Laws of Boolean Algebra, but we have only covered according to I.S.C. XII Syllabus.
Following are the laws which we will cover:
1 | Property of "0" | A + 0 = A A . 0 = 0 |
2 | Property of "1" | A + 1 = 1 A . 1 = A |
3 | Idempotence Law | A + A = A A . A = A |
4 | Involution Law | (A')' = A |
5 | Complementarity Law | A + A' = 1 A . A' = 0 |
6 | Commutative Law | A + B = B + A A . B = B . A |
7 | Associative Law | ( A + B ) + C = A + ( B + C ) ( A . B ) . C = A . ( B . C ) |
8 | De-Morgan's Law | ( A + B )' = A' . B' ( A . B )' = A' + B' |
9 | Distributive Law | A . ( B + C ) = A.B + A.C A + ( B.C ) = ( A+B ). ( A+C ) |
10 | Absorption Law | A + A.B = A A . ( A + B ) = A |
11 | Redundancy Law | A + A'. B = A + B A . ( A' + B ) = A + B |
1) Property of "0":
1) A + 0 = A
A | “0” | A+0 |
0 | 0 | 0 |
1 | 0 | 1 |
2) A . 0 = 0
A | “0” | A.0 |
0 | 0 | 0 |
1 | 0 | 0 |
2) Property of "1":
1) A + 1 = 1
A | “1” | A+1 |
0 | 1 | 1 |
1 | 1 | 1 |
2) A . 1 = A
A | “1” | A.0 |
0 | 1 | 0 |
1 | 1 | 1 |
3) Idempotence Law:
This law states that OR/ AND of a variable with itself is always equal to the variable.
1) A + A = A
2) A . A = A
The same can be expressed using following truth table:
A | A | A + A | A . A |
0 | 0 | 0 | 0 |
1 | 1 | 1 | 1 |
4) Involution Law:
This law states that double complement of a variable is always equals to that variable.
(A')' = A
This can be understood by following truth table:
A | A’ | (A’)’ |
0 | 1 | 0 |
1 | 0 | 1 |
5) Complemetarity Law:
Complementarity Law states 2 rules:
Rule 1: "OR" of a variable with its complement is always equal to 1
A + A' = 1
A | A’ | A + A’ |
0 | 1 | 1 |
1 | 0 | 1 |
Rule 2: "AND" of a variable with its complement is always equal to 0
A . A' = 0
A | A’ | A . A’ |
0 | 1 | 0 |
1 | 0 | 0 |
6) Commutative Law:
This law states that the order of the variables connected using OR/ AND makes no
difference
1) A+B = B+A
Below Truth Tables prove the above laws:
A | B | A + B | B + A |
0 | 0 | 0 | 0 |
0 | 1 | 0 | 0 |
1 | 0 | 0 | 0 |
1 | 1 | 1 | 1 |
2) A.B = B.A
A | B | A . B | B . A |
0 | 0 | 0 | 0 |
0 | 1 | 0 | 0 |
1 | 0 | 0 | 0 |
1 | 1 | 1 | 1 |
7) Associative Law :
This law states that when more than two variables are connected using OR/ AND, the result is the same regardless of the grouping of the variables.
2) A . ( B.C ) = ( A.B ).C
Below Truth Table illustrates these laws as applied to 3-input OR gates.
1) A + (B + C) = (A + B) + C
(1) | (2) | |||||
A | B | C | B+C | A+(B+C) | A+B | (A+B)+C |
0 | 0 | 0 | 0 | 0 | 0 | 0 |
0 | 0 | 1 | 1 | 1 | 0 | 1 |
0 | 1 | 0 | 1 | 1 | 1 | 1 |
0 | 1 | 1 | 1 | 1 | 1 | 1 |
1 | 0 | 0 | 0 | 1 | 1 | 1 |
1 | 0 | 1 | 1 | 1 | 1 | 1 |
1 | 1 | 0 | 1 | 1 | 1 | 1 |
1 | 1 | 1 | 1 | 1 | 1 | 1 |
You can easily see that Col (1) & Col (2) have same values, thus verifying the Law.
2) A . ( B.C ) = ( A.B ).C
(1) | (2) | |||||
A | B | C | B.C | A.(B.C) | A.B | (A.B).C |
0 | 0 | 0 | 0 | 0 | 0 | 0 |
0 | 0 | 1 | 0 | 0 | 0 | 0 |
0 | 1 | 0 | 0 | 0 | 0 | 0 |
0 | 1 | 1 | 1 | 0 | 0 | 0 |
1 | 0 | 0 | 0 | 0 | 0 | 0 |
1 | 0 | 1 | 0 | 0 | 0 | 0 |
1 | 1 | 0 | 0 | 0 | 1 | 0 |
1 | 1 | 1 | 1 | 1 | 1 | 1 |
here also Col (1) & Col (2) have same values, thus verifying the Law.
8) De-Morgan's Law :
1) (A + B)' = A' . B' | 1 | 2 | ||||
A | B | A' | B' | A.B | (A.B)' | A' + B' |
0 | 0 | 1 | 1 | 0 | 1 | 1 |
0 | 1 | 1 | 0 | 0 | 1 | 1 |
1 | 0 | 0 | 1 | 0 | 1 | 1 |
1 | 1 | 0 | 0 | 1 | 0 | 0 |
2) (A . B)' = A' + B' | 1 | 2 | ||||
A | B | A' | B' | A+B | (A+B)' | A' . B' |
0 | 0 | 1 | 1 | 0 | 1 | 1 |
0 | 1 | 1 | 0 | 1 | 0 | 0 |
1 | 0 | 0 | 1 | 1 | 0 | 0 |
1 | 1 | 0 | 0 | 1 | 0 | 0 |
In both the tables you can see that col. 1 = col. 2, hence proving the laws.
9) Distributive Law:
This law states that for any given 3 or more variables, following relation establishes:
1) A(B + C) = AB + AC
2) A + B.C = (A+B).(A+C)
Let us prove both the laws by using a truth tables;
1) A(B + C) = AB + AC
(1) | (2) | ||||||
A | B | C | B+C | A.(B+C) | A.B | A.C | AB + AC |
0 | 0 | 0 | 0 | 0 | 0 | 0 | 0 |
0 | 0 | 1 | 1 | 0 | 0 | 0 | 0 |
0 | 1 | 0 | 1 | 0 | 0 | 0 | 0 |
0 | 1 | 1 | 1 | 0 | 0 | 0 | 0 |
1 | 0 | 0 | 0 | 0 | 0 | 0 | 0 |
1 | 0 | 1 | 1 | 1 | 0 | 1 | 1 |
1 | 1 | 0 | 1 | 1 | 1 | 0 | 1 |
1 | 1 | 1 | 1 | 1 | 1 | 1 | 1 |
here col. 1 is equals to col.2, hence proving the law
2) A + B.C = (A+B).(A+C)
(1) | (2) | ||||||
A | B | C | B.C | A+ B.C | A+B | A+C | (A+B). (A+C) |
0 | 0 | 0 | 0 | 0 | 0 | 0 | 0 |
0 | 0 | 1 | 0 | 0 | 0 | 1 | 0 |
0 | 1 | 0 | 0 | 0 | 1 | 0 | 0 |
0 | 1 | 1 | 1 | 1 | 1 | 1 | 1 |
1 | 0 | 0 | 0 | 1 | 1 | 1 | 1 |
1 | 0 | 1 | 0 | 1 | 1 | 1 | 1 |
1 | 1 | 0 | 0 | 1 | 1 | 1 | 1 |
1 | 1 | 1 | 1 | 1 | 1 | 1 | 1 |
here also col. 1 is equals to col.2, thus verifying the Law.
10) Absorption Law:
This law states following 2 rules:
A | B | A.B | A+( A.B) |
0 | 0 | 0 | 0 |
0 | 1 | 0 | 0 |
1 | 0 | 0 | 1 |
1 | 1 | 1 | 1 |
A | B | A+B | A.(A+B) |
0 | 0 | 0 | 0 |
0 | 1 | 1 | 0 |
1 | 0 | 1 | 1 |
1 | 1 | 1 | 1 |
11) Redundancy Law :
This law states following 2 rules:
A | B | A’ | A’. B | A+ B | A+ (A’. B) |
0 | 0 | 1 | 0 | 0 | 0 |
0 | 1 | 1 | 1 | 1 | 1 |
1 | 0 | 0 | 0 | 1 | 1 |
1 | 1 | 0 | 0 | 1 | 1 |
A | B | A’ | A’+ B | A.B | A. (A’+ B) |
0 | 0 | 1 | 1 | 0 | 0 |
0 | 1 | 1 | 1 | 0 | 0 |
1 | 0 | 0 | 0 | 0 | 0 |
1 | 1 | 0 | 1 | 1 | 1 |
No comments:
Post a Comment